Licensing of artisanal mining on private land in Uganda: social and economic implications for female spouses and women entrepreneurs - Sebina-Zziwa, Abby; Kibombo, Richard (Canadian Journal of African Studies/Revue canadienne des études africaines, 2020)
Based on research conducted from October 2015 through June 2018, this paper highlights the social and economic implications of licensing artisanal mining on women’s land rights in Uganda. It also brings to the fore how artisanal and small-scale mining (ASM) governance is affecting women’s participation in the sector. It examines how women as spouses and as entrepreneurs in the ASM sector are affected by the prevailing local governance structures and land tenure arrangements; the arrangements in place to ensure that female spouses get a share of compensation and other long-term benefits from ASM; and the ramifications of the lacuna between policy and enforcement on spouses and on women engaged in the ASM sector. The results show that the rights of women in the ASM sector are subjugated to social cultural practices, contradictory laws regarding women’s land rights, poor law enforcement, and weak structures for ASM governance.
Keywords: Private registered land; artisanal mining; women’s surface rights; legal pluralism; hybrid governance